Les déterminants de la dynamique spatiale de la ville de Bingerville (sud de la Côte d'Ivoire) de 1960 à nos jours - Akou Don Franck Valéry Loba (EchoGéo)
This article reports on the spatial dynamics of Bingerville, a historic city in southern Côte d'Ivoire. The study aims to examine data on the nature of the determinants of this dynamic space. The cartographic sources from aerial missions were allowed to synthesize spatial dynamics. A survey of the technical department of the council has provided information on land management.In 1960, the date of declaration of independence until 1985, despite the interventions of the welfare state, the growth of the urban stain was very insignificant. A commitment to the state to build a modern city, opposed the distrust and hostility of the indigenous, fearing possible expropriations.During the period of economic recession, marked by the advent of structural adjustment programs, the process of urbanization Bingerville will experience a revival. The institutional changes that occurred after 1985 which saw the emergence of new local authorities in this case the county, there are many. The communalisation, building on the agenda involve the population in autocthtones mechanisms of creation of urban land, managed to regain the momentum of developments. Thus, under the impetus of private real estate operators, the city has seen in addition to its original core of new neighborhoods, it has since met with stretching toward its northern and western suburbs and become part of the front of urbanization East of the city of Abidjan.